Impact of Information Communication Technology on Secondary School Administration in Federal Capital Territory, Abuja, Nigeria - Olowonefa G. S (International Journal on Integrated Education, 2022)
This study investigated impact of Informational Communication Technology (ICT) on public secondary school administration in FCT, Abuja, Nigeria. The objectives of this study were to assess the impact of ICT on public secondary school administration in FCT, Abuja and also to find out the challenges preventing the use of ICT in public secondary school administration in FCT, Abuja, Nigeria. The study adopted survey research design. The population of the study consisted of all senior secondary school administrators (Principals, Vice-Principals, Heads of Departments and Administrative officers). The sample size of the study was 150 respondents. The multi-stage sampling technique was used to select the respondents for the study. The researcher developed an instrument for the study titled “Impact of ICT on Public Secondary School Administration Questionnaire” (IIPSSAQ). Reliability of instrument was ascertained by three lectures in Nasarawa State University and the Validity of the instrument was established using the Kinder Richardson Formula with index value of 0.83. The data collected was analyzed using simple descriptive statistics of mean and standard deviation to answer research questions. The findings of the study revealed that ICT makes school administration effective and efficient, makes the sending and replying of memo fast, makes storage of school data secured and retrievable, makes students registration, improves the planning, organizing, coordinating and controlling of school programme and ICT makes communication between principals and teachers fast and accurate. The result also indicated that shortage of funds, inadequate ICT facilities, unstable internet services, unstable power supply, poor ICT knowledge, poor implementation of ICT policies, high cost of ICT facilities and high cost of internet services were the challenges preventing the use of ICT in public secondary schools in FCT. Based on these findings, the study hereby recommends that government and other stakeholders of public secondary schools should ensure that principals are trained to improve their levels of competencies on the use of ICT so as to meet up with the global practices in school administration. Also government should ensure adequate funding and adequate ICT facilities with strong internet connectivity that can ensure effective and efficient secondary school administration. In addition there should be power backup in case of power failure. Again, the government should ensure that ICT policies are well implemented in public secondary schools.